Instability of horizontally and vertically sheared parallel flow - Ringerud, Mark A., author; Stevens, Duane E., author; Ciesielski, Paul E., author (Colorado State University. Libraries, 1989)
This study examines the effects of various windshears on the perturbation growths within inertially unstable regions. A primary focus is determining what type of instability is preferred, symmetric or asymmetric, through the development of a two-dimensional model using the primitive equations and a jet with horizontally and vertically sheared flow. A necessary condition for inertial instability is when the basic state potential vorticity, f P < 0. The potential vorticity can be viewed as having two influences, that due to the horizontal wind shear and vertical shear. With this in mind, I examine the relationship between the shears in inertial instability. This study extends previous results where the basic state contained only horizontal shear, u(y). These results, obtained with a shallow water model, showed that asymmetric modes had larger growth rates than symmetric modes. By examining various jet profiles which contained both horizontal and vertical shear, the results in this more general case (i.e., u(y, z) again revealed that asymmetric instabilities are preferred.
June 1989.
Also issued as Mark A. Ringerud's thesis (M.S.) -- Colorado State University, 1988.
Keywords: Wind shear; Vertical wind shear; Dynamic meteorology -- Mathematical models